"Infiltrators" or Refugees? An Analysis of Israel's Policy Towards African Asylum‐Seekers. (15th April 2013) - Yaron, Hadas; Hashimshony‐Yaffe, Nurit; Campbell, John
Abstract This article adopts a genealogical approach in examining Israeli immigration policy by focusing on the situation confronting African asylum seekers who have been forced back into Egypt, detained and deported but who have not had their asylum claims properly assessed. Based on immigration policies formulated at the time of Israeli independence, whose principle objective was to secure a Jewish majority state, we argue that Israel's treatment of African asylum seekers as 'infiltrators'/economic migrants stems from an insistence on maintaining immigration as a sovereign issue formally isolated from other policy domains. Such an approach is not only in violation of Israel's commitment to the Refugee Convention, it directly contributes to policies which are ineffective and unduly harsh.